2004
DOI: 10.4049/jimmunol.172.11.6751
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Two Avian (Quail and Chicken) MHC Regions

Abstract: We mapped two different quail Mhc haplotypes and sequenced one of them (haplotype A) for comparative genomic analysis with a previously sequenced haplotype of the chicken Mhc. The quail haplotype A spans 180 kb of genomic sequence, encoding a total of 41 genes compared with only 19 genes within the 92-kb chicken Mhc. Except for two gene families (B30 and tRNA), both species have the same basic set of gene family members that were previously described in the chicken “minimal essential” Mhc. The two Mhc regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 62 publications
5
131
0
Order By: Relevance
“…BLAST search approaches in chicken, turkey, quail, black grouse, and zebra finch failed to detect genes for immuno-and thymoproteasome, suggesting that they have been lost in the lineage of birds (Balakrishnan et al 2010;Chaves et al 2009;Shiina et al 2007;Shiina et al 2004;Sutoh et al 2012;Wang et al 2012). While the genes coding for the catalytic subunits β1i and β5i are present in the class II region of the human and murine MHC loci, sequence searches in chicken genome databases revealed that there are no LMP genes in the avian MHC region, and also the immune subunit β2i could not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…BLAST search approaches in chicken, turkey, quail, black grouse, and zebra finch failed to detect genes for immuno-and thymoproteasome, suggesting that they have been lost in the lineage of birds (Balakrishnan et al 2010;Chaves et al 2009;Shiina et al 2007;Shiina et al 2004;Sutoh et al 2012;Wang et al 2012). While the genes coding for the catalytic subunits β1i and β5i are present in the class II region of the human and murine MHC loci, sequence searches in chicken genome databases revealed that there are no LMP genes in the avian MHC region, and also the immune subunit β2i could not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Japanese quail have a series of duplications yielding seven MHC class I genes and at least four expressed genes (although only two appear to be classical class I MHC) (23)(24)(25). However, the Inoko group has since published that only one of these two expressed classical loci is highly expressed (26), much like the chicken.…”
mentioning
confidence: 99%
“…Gene duplication among MHC-I genes has also been observed in many other representative vertebrates such as Atlantic salmon , frogs (Kiemnec-Tyburczy et al, 2012), birds (Shiina et al, 2004), iguanas (Glaberman and Caccone, 2008), and saltwater crocodile (Jaratlerdsiri et al, 2012;2014). Meanwhile, we found two putative pseudogenes, which contain premature stop codons.…”
Section: Xiuyun Yuan Et Al Mhc Class I Exon 4 In Eremias Multiocellatamentioning
confidence: 75%
“…So far, data from the α3 domain are frequently used to recover evolutionary relationships among class I sequences across species because they are relatively conserved in comparison to the two peptide-binding domains (α1, α2), which are often under balancing selection. MHC class I has been wellstudied in mammals (Kelley et al, 2005), birds (Shiina et al, 2004), and fishes (Shand and Dixon, 2001;Kulski et al, 2002). However, there is still limited knowledge of the MHC in non-avian reptiles, particularly in the key group of squamates.…”
Section: Introductionmentioning
confidence: 99%